Discounting of outcomes in which immediate gains are followed by delayed losses. Issue 1 (13th December 2022) - Estle, Sara J.; Green, Leonard; Myerson, Joel; Yeh, Yu‐Hua
Abstract : Previous discounting research has focused on relatively simple situations (e.g., choosing between immediate and delayed gains, or between immediate and delayed losses) and the relations among amount, delay, and subjective value in such situations are now well established. Many everyday choice situations, however, are more complex, involving alternatives that combine gains and losses. In two experiments, participants discounted a monetary outcome that combined an immediate gain with a delayed loss. Consistent with the discounting framework, the value of the combination was approximately equal to the difference between the (undiscounted) value of the immediate gain and the (discounted) value of the delayed loss. More precise predictions of the relative subjective value of the delayed loss component of a combination were given by the same hyperboloid function that describes discounting in simple choice situations where outcomes only involve gains or losses, not both. As in previous studies, when the outcome was a simple one consisting of only a delayed loss, discounting was not affected by the amount of that loss. Surprisingly, however, when the loss was preceded by a gain, the degree to which the combination was discounted was affected by the amount of the loss. Notably, discounting of the delayed loss component of the combination decreased with the amount of the loss in a fashion similar to that observed with simple delayed gains, where smaller amounts are discounted more steeply than larger amounts. Choice situations involving immediate gains followed by delayed losses pose iconic self‐control problems, and the present findings support the application of the discounting framework to these important everyday problems.